(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Consumer behavior is a complex, dynamic, multidimensionalprocess, and all marketing decisions are based on assumptions about consumerbehavior. Marketing strategy is the game plan which the firms must adhere to,in order to outdo the competitor or the plans to achieve the desired objective.In formulating the marketing strategy, product effectively, cost-benefitanalysis must be undertaken. In this paper we studied consumer perception factors.